Naltrexone Prevents in Males and Attenuates in Females the Expression of Behavioral Sensitization to Ethanol Regardless of Maternal Separation - Kawakami, Suzi E.; Quadros, Isabel M. H.; Suchecki, Deborah (Frontiers in Endocrinology, 2016)
Maternal separation alters the activity of the opioid system, which modulates ethanol-induced stimulation and behavioural sensitization. This study examined the effects of an opioid antagonist, naltrexone, on the expression of behavioural sensitization to ethanol in adult male and female mice submitted to maternal separation from postnatal days (PNDs) 2 to 14. Whole litters of Swiss mice were either not separated (animal facility rearing, AFR) or separated from their mothers for 3 h (long maternal separation, LMS). Starting in PND 90, male and female AFR and LMS mice received daily i.p. injections of saline (SAL) or ethanol (EtOH, 2.2 g/kg) for 21 days. Locomotor activity was assessed in cages containing photoelectric beams, once a week, to examine the development of behavioural sensitization. Five days after the end of the chronic treatment, animals were submitted to four locomotor activity tests spaced by 48 h, to assess the expression of behavioural sensitization. In all tests, animals received two i.p. injections with a 30 min interval and were then assessed for locomotor response to different treatment challenges, which were: SAL/SAL, SAL/EtOH (2.2 g/kg), naltrexone (NTX) 2.0 mg/kg (NTX2)/EtOH and NTX 4.0 mg/kg (NTX4)/EtOH. Regardless of maternal separation, EtOH-treated male and female mice displayed increased locomotor responses to EtOH during the 21-day treatment, indicating the development of behavioural sensitization. In the SAL/EtOH challenge, EtOH-treated LMS and AFR male and female mice exhibited higher locomotor activity than their SAL-treated counterparts, indicating the expression of sensitization. The co-administration of either dose of NTX blocked the expression of locomotor sensitization in both AFR and LMS male mice with a history of EtOH sensitization. In females, a significant attenuation of EtOH sensitization was promoted by both NTX doses, while still maintaining an augmented stimulant response to EtOH. Importantly, maternal separation did not interfere in this phenomenon. These results indicate that expression of behavioural sensitization was importantly modulated by opioidergic mechanisms both in male and female mice and that maternal separation did not play a major role in either development or expression of this EtOH sensitization.